Pirolisis Kayu Akasia Menjadi Bio-Oil Menggunakan Katalis NiMo/NZA Dengan Variasi Jumlah Pengembanan Logam Dan Rasio Berat Katalis Terhadap Biomassa - Saputra, Adika; Bahri, Syaiful; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The purpose of this research is to determine the effect of the percentage of NiMo and ratio of NiMo/NZA catalyst to the yield of bio-oil in the synthesis of bio-oil from acacia wood using pyrolysis methode. The process was carried out using 50 gram, of acacia wood, 500 ml silinap and NiMo/NZA catalyst with various variations of the percentage of NiMo metal 0%, 1%, 2%, 3% and the variation ratio of NiMo/NZA catalyst 3%, 6%, 12% respectively of the biomass having a stirring speed of 300 rpm and a temperature of 320 ºC for 120 minutes. From the result, the highest yield (69.41%) was obtained of NiMo ratio 2% and the catalyst 3%. The physical properties at the bio-oil result obtained density 0.938 gr/ml, viscosity 1.919 cSt, acid number 87.593 mg NaOH/gr sample, and the flash point 55 oC respectively. From analysis by the GC-MS, the dominant components were 2-Pentene,2,4,4-Trimethyl (18.50%), Pentane,2,2,4,4-Tetramethyl- (5.64%), 1-Pentene,2,4,4-Trimethyl- (10.31%), 2-Pentene,2,3, 4-Trimethyl- (2.43%) and Cyclohexanone,3-(3,3-Dimethylbutyl) (8.08%) were found.Keywords: Biomass, Bio-oil, NiMo/NZA, acacia wood, Pyrolysis